Surviving on a mountain of rubbish: The state and access to health social security for female scavengers - Fairus Dwi Putri; Khaerul Umam Noer (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2020)
This paper focuses on the lives of women scavengers heads of households and how the state guarantees the fulfillment of the right to health. Women are relatively more vulnerable to various risks related to their life cycle and role in the family; thus, their access to health insurance is an obligation that must be met by the government. This paper has two objectives: to map social life and, at the same time, analyze the accessibility of the Healthy Indonesia National Health Insurance Card for female head of household scavengers in TPA Cipayung, Depok City. Using qualitative methods, and focusing on five dimensions of accessibility: availability, accessibility, accommodation, affordability, and acceptance, this study found that all health insurance arrangements are still very problematic. Even though these women scavengers are protected by JKN-KIS PBI, in reality, they are still challenging to get access to health services, ranging from the availability of doctors, the scarcity of drugs, to the discrimination of health services. This shows that they have not yet received full health insurance, which has a direct impact on the social and economic lives of the scavengers.